Residues flanking the ARKme3T/S motif allow binding of diverse targets to the HP1 chromodomain: Insights from molecular dynamics simulations - Pokorná, Pavlína; Krepl, Miroslav; Šponer, Jiří (Biochimica et biophysica acta. G, General subjects, 2021)
BACKGROUND: The chromodomain (CD) of HP1 proteins is an established H3K9me3 reader that also binds H1, EHMT2 and H3K23 lysine-methylated targets. Structural experiments have provided atomistic pictures of its recognition of the conserved ARKme3S/T motif, but structural dynamics' contribution to the recognition may have been masked by ensemble averaging. METHODS: We acquired ~350 μs of explicit solvent molecular dynamics (MD) simulations of the CD domain interacting with several peptides using the latest AMBER force fields. RESULTS: The simulations reproduced the experimentally observed static binding patterns well but also revealed visible structural dynamics at the interfaces. While the buried K0me3 and A-2 target residues are tightly bound, several flanking sidechains sample diverse sites on the CD surface. Different amino acid positions of the targets can substitute for each other by forming mutually replaceable interactions with CD, thereby explaining the lack of strict requirement for cationic H3 target residues at the -3 position. The Q-4 residue of H3 targets further stabilizes the binding. The recognition pattern of the H3K23 ATKme3A motif, for which no structure is available, is predicted. CONCLUSIONS: The CD reads a longer target segment than previously thought, ranging from positions -7 to +3. The CD anionic clamp can be neutralized not only by the -3 and -1 residues, but also by -7, -6, -5 and +3 residues. GENERAL SIGNIFICANCE: Structural dynamics, not immediately apparent from the structural data, contribute to molecular recognition between the HP1 CD domain and its targets. Mutual replaceability of target residues increases target sequence flexibility.
Keywords: histony; Protein Binding; Chromosomal Proteins, Non-Histone; histonlysin-N-methyltransferasa; simulace molekulární dynamiky; interakční proteinové domény a motivy; Histone-Lysine N-Methyltransferase; posttranslační úpravy proteinů; Methylation; metylace; Molecular Dynamics Simulation; Amino Acid Sequence; Protein Processing, Post-Translational; Histocompatibility Antigens; lysin; Lysine; Protein Interaction Domains and Motifs; vazba proteinů; lidé; Humans; histokompatibilní antigeny; sekvence aminokyselin; chromozomální proteiny, nehistonové; Histones